Introducing Korean Popular Culture (Taylor & Francis, 2023)
Given the phenomenal popularity of mukbang (a live-streamed eating show) among young people, first in Korea and now globally, it is no longer a secret that they like to watch other people eating and cooking in the digital age. This chapter provides an overview of the evolution of mukbang culture in Korea while exploring the sociocultural meanings of this new cultural phenomenon. The chapter suggests that mukbang as a social phenomenon is deeply rooted in the precarious contexts of Korean youth, also known as the ingyeo generation. Young people's increasing engagement with mukbang illustrates how a shifting sociocultural structure engages with an emerging affective structure through digital mediation. Young Koreans' negotiation of their precarious present and future through vicarious experiences of binge eating implies how the basic needs of eating are mediated, spectacularized and resignified as a subcultural practice.
English
Keywords: Media studies; Popular culture; Korean popular culture, BTS, Parasite, Squid Game, K-Pop, Korean Wave, Hallyu, K-Drama, Social media age